Effectiveness of Hatha Yoga in The Recovery of Bullying Post Trauma - Putu Sri Marselinawati; I Nyoman Agus Pradnya Wiguna; I Gede Agus Suparta; Ni Nengah Sudarsini (Journal of International Conference Proceedings, 2025)
Bullying has a serious impact on the mental health of children and adolescents, including anxiety, depression, post-traumatic stress, and decreased self-esteem. Mind–body interventions such as Hatha Yoga are considered effective in supporting recovery by strengthening emotional regulation and psychological balance. This study aims to examine the effectiveness of Hatha Yoga in the recovery of bullying victims through a literature review using the PEOS framework. The search was conducted through PubMed with the keywords “Yoga” and “Mental Health,” covering publications from the last five years with clinical trial and randomized controlled trial designs.. The studies also confirm the feasibility and acceptability of yoga as a non-pharmacological intervention for adolescents and university students. Given its feasible, acceptable, and low-risk nature, Hatha Yoga can be integrated into school and community programs as both a preventive and curative strategy. Further randomized controlled trials specifically targeting bullying victims are required to strengthen the empirical evidence.